Identities of the millipede genera Skleroprotopus Attems, 1901 and Ansiulus Takakuwa, 1940 (Diplopoda: Julida: Mongoliulidae), with emphasis on the postembryonic development of Skleroprotopus coreanus (Pocock, 1895) - Mikhaljova, Elena V. (Zootaxa, 2019)
Based on a study of postembryonic growth of Skleroprotopus coreanus (Pocock, 1895), the following new synonyms and combinations are proposed: Skleroprotopus Attems, 1901 = Ansiulus Takakuwa, 1940, syn. n., Skleroprotopus coreanus (Pocock, 1895) = Skleroprotopus schmidti Golovatch, 1979, syn. n., Skleroprotopus aberrans (Mikhaljova & Korsós, 2003), comb. n. = Ansiulus aberrans Mikhaljova & Korsós, 2003; Skleroprotopus legitimus (Golovatch, 1980), comb. n. = Ansiulus legitimus (Golovatch, 1980); Skleroprotopus deminutus (Mikhaljova, 2001), comb. n. = Ansiulus deminutus Mikhaljova, 2001; Skleroprotopus matumotoi (Takakuwa, 1940), comb. n. = Ansiulus matumotoi Takakuwa, 1940, the valid names being the former. 13 postembryonic stadia of males of Skleroprotopus coreanus were revealed: sexual dimorphism appears at stadium VIII, maturity is achieved in stadium XI.